(untitled) (Research, Society and Development, 2024)
The present study aimed to investigate how the use of telemonitoring can enhance the provision of dental care. Data collection was conducted through a questionnaire. Secondary sources from clinical records were used to determine the prevalence of caries and periodontal disease in the studied population. The data were analyzed descriptively using measures of central tendency and variability, and inferentially through association tests. Additionally, underlying diseases were classified according to the modified Santos and Haddad classification. Among the 97 parents/guardians who participated, 91.8% were female, with a mean age of 39 years. The most predominant age group among the patients in the study was one to five years old, with males representing 50.5% of the sample. The most represented classification of underlying disease was systemic conditions and diseases. Clinical record data showed significant rates of the absence of dental caries (49.5%) and periodontal disease (75.3%). Regarding the need for emergency care, only 13.4% of parents/guardians reported a need to seek dental services for their child. These findings enable more efficient management for appointment scheduling, improved care, and increased collaboration from parents or guardians in preventing oral diseases. Therefore, telemonitoring can be an effective tool in the preventive clinical monitoring plan for pediatric patients with disabilities.